Peran Orang Tua terhadap Nafkah Anak yang Menjanda pada Masyarakat Ketapang, Mentawa Baru Ketapang, Kotawaringin Timur, Kalimantan Tengah - Wahidah, Sofia Maulina; Habibi, Ahyat (AS-SABIQUN, 2023)
The role of parents in the livelihood of a widowed child, who is located in the Ketapang Village, Mentawa Baru Ketapang, Central Kalimantan. This research is motivated by the opinion of some people that children who are widowed or divorced from their husbands are no longer the responsibility of their parents. Based on the Qur'an and Hadith, the maintenance of a widowed child is the obligation of the close relatives of the father and mother, furu' sons and hawashi brothers. The purpose of this research is to find out the role of parents in providing for children who are widows in the Ketapang community, Mentawa Baru Ketapang, East Kotawaringin, Central Kalimantan. And the factors that influence whether or not the livelihood of a widowed child is fulfilled in the Ketapang community, Mentawa Baru Ketapang, East Kotawaringin, Central Kalimantan. This study uses a qualitative approach with a case study type of research. The selection of research subjects was carried out using a purposive sampling technique, namely two families. Methods of data collection is done by using interviews, observation, and documentation. The data validity test was carried out using the source triangulation method. The results of the study show that there are two roles of parents in supporting widowed children, namely: a. Parents who continue to provide for their children. b. Parents who do not provide for their children. The factors are divided into two, namely: a. Factors of parents who continue to provide a living for children who are widows in the Ketapang community, Mentawa Baru Ketapang, East Kotawaringin, Central Kalimantan. b. Factors of parents who do not provide a living for children who are widows in the Ketapang community, Mentawa Baru Ketapang, East Kotawaringin, Central Kalimantan.